2018
DOI: 10.1242/jcs.203950
|View full text |Cite
|
Sign up to set email alerts
|

The triple helix of collagens – an ancient protein structure that enabled animal multicellularity and tissue evolution

Abstract: The cellular microenvironment, characterized by an extracellular matrix (ECM), played an essential role in the transition from unicellularity to multicellularity in animals (metazoans), and in the subsequent evolution of diverse animal tissues and organs. A major ECM component are members of the collagen superfamily -comprising 28 types in vertebrates - that exist in diverse supramolecular assemblies ranging from networks to fibrils. Each assembly is characterized by a hallmark feature, a protein structure cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
125
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(138 citation statements)
references
References 264 publications
(243 reference statements)
1
125
0
12
Order By: Relevance
“…Collagen structure is formed of three twisted polypeptides, and called a triple helix. Each polypeptide chain possesses a characteristic major tripeptide repeat (GPX) sequence with glycine (G), proline (P), and several different amino acids (X) ( Figure a) 120–125. It was found that the piezoelectricity of collagen is due to this particular helical structure 13,126–129.…”
Section: Piezoelectricity Of Proteinsmentioning
confidence: 99%
“…Collagen structure is formed of three twisted polypeptides, and called a triple helix. Each polypeptide chain possesses a characteristic major tripeptide repeat (GPX) sequence with glycine (G), proline (P), and several different amino acids (X) ( Figure a) 120–125. It was found that the piezoelectricity of collagen is due to this particular helical structure 13,126–129.…”
Section: Piezoelectricity Of Proteinsmentioning
confidence: 99%
“…[1] Here,the stored information serves as as timulus that triggers the transition from al ower-order structure to ah igher-order superstructure. [2] Thet ransition of the initial helical architectures to superhelical systems is generally accompanied by chirality inversion, and as aresult of this,the helicity of the superhelix differs from that of the helical building blocks. [3] Forexample, collagen-a right-handed superhelix which provides strength to rigid and complainttissues,isgenerated via the assembly of three left-handed helices.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Forexample, collagen-a right-handed superhelix which provides strength to rigid and complainttissues,isgenerated via the assembly of three left-handed helices. [2] Another interesting case is the tobacco mosaic virus (TMV) in which protein molecules of the virus and DNAs pontaneously generate ar ight-handed helical structure. [4] Thep ursuit of researchers to mimic the precision, accuracy,a nd efficiencyo fb iological functions of natural superhelical systems has resulted in the development of nature-inspired synthetic helices [3] that have many applications in the fields of chiral recognition, catalysis,and material science.…”
Section: Introductionmentioning
confidence: 99%
“…This compromises the overall tissue integrity and leads to rupture of blood vessel walls and hemorrhages. Besides providing structural support, collagens also give signaling cues to cells and may regulate cell proliferation, apoptosis, angiogenesis, invasion, and metastasis (Fidler et al , ; Nissen et al , ; Wu and Ge, ). Further, our results show that P4HA1 knockdown reduced the secretion of CTHRC1, an important mediator of melanoma cell migration and invasion, in vitro and its deposition around tumor blood vessels in vivo , suggesting that this angiogenesis‐promoting molecule may also play an important role in P4HA1‐regulated neovascularization.…”
Section: Discussionmentioning
confidence: 99%